2021
DOI: 10.1182/bloodadvances.2021005614
|View full text |Cite
|
Sign up to set email alerts
|

Gilteritinib-induced upregulation of S100A9 is mediated through BCL6 in acute myeloid leukemia

Abstract: Drug resistance and relapse are common challenges in acute myeloid leukemia (AML), particularly in an aggressive subset bearing internal tandem duplications (ITD) of the FLT3 receptor (FLT3-ITD+). The tyrosine kinase inhibitor gilteritinib is approved for the treatment of relapse/refractory AML with FLT3 mutations, yet resistance to gilteritinib remains a clinical concern of which the underlying mechanisms remain incompletely understood. Using transcriptomic analyses and functional validation studies, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A novel IRAK1/IRAK4/FLT3 tri-selective inhibitor eradicated adaptively resistant AML clones in liquid culture and xenografts [142,143]. Two subsequent studies reiterate innate immune activation [144] and upregulation of the TLR ligand S100A9 [145], respectively, as mediators of adaptive response to the FLT3 inhibition in AML. Du et al [146 & ] report that treatment with Ara-C or anthracyclines induces a subpopulation of leukemic cells to acquire an inflammatory signature and senescence-like state that enables chemoresistance and disease recurrence.…”
Section: Interleukin 1 Receptor-associated Kinase Inhibitors To Overc...mentioning
confidence: 99%
“…A novel IRAK1/IRAK4/FLT3 tri-selective inhibitor eradicated adaptively resistant AML clones in liquid culture and xenografts [142,143]. Two subsequent studies reiterate innate immune activation [144] and upregulation of the TLR ligand S100A9 [145], respectively, as mediators of adaptive response to the FLT3 inhibition in AML. Du et al [146 & ] report that treatment with Ara-C or anthracyclines induces a subpopulation of leukemic cells to acquire an inflammatory signature and senescence-like state that enables chemoresistance and disease recurrence.…”
Section: Interleukin 1 Receptor-associated Kinase Inhibitors To Overc...mentioning
confidence: 99%
“…They further verified S100A8 as a marker for poor prognosis with a specificity of 75% and a sensitivity of 70% for death prediction. Notably, previously mentioned transcriptomics-based studies found elevated expression of S100A8 gene in samples treated with FLT3 inhibitors and its level might be associated with resistance to FLT3 inhibitors [ 88 ]. Higher expression of S100A8 gene was also related to poor prognosis and chemotherapy resistance in de novo AML [ 89 ].…”
Section: Omics In Diagnosis Of Amlmentioning
confidence: 99%
“…Analysis of the relationship between gene expression and response to sorafenib revealed that patients with high HIF expression had better responses. Zavorka et al [ 88 ]. applied transcriptomic analyses to identify the alternative mechanisms of gilteritinib resistance based on FLT3-ITD mutant murine models.…”
Section: Omics In Aml Treatmentmentioning
confidence: 99%
“…Increased activity of multiple S100 family members is associated with increased drug resistance in hematologic malignancies including AML, CML, ALL, and B-cell lymphomas ( 302 , 303 ). For example, S100-A8/A9 contribute to gilteritinib resistance in FLT3- internal tandem duplications- (FLT3-ITD)-positive AML primary cells and cell lines ( 304 ). Particularly, S100-A9 expression has been found to be more consistently and remarkably altered than S100-A8 in human FLT3-ITD-positive AML cell lines (MOLM13 and MOLM13-RES) after gilteritinib treatment.…”
Section: Calcium Signaling Deregulation In Blood Cancermentioning
confidence: 99%
“…Particularly, S100-A9 expression has been found to be more consistently and remarkably altered than S100-A8 in human FLT3-ITD-positive AML cell lines (MOLM13 and MOLM13-RES) after gilteritinib treatment. The potential mechanism is gilteritinib promotes Bcl-6 dissociation from the S100-A9 promoter, which leads to upregulation of S100-A9 ( 304 ).…”
Section: Calcium Signaling Deregulation In Blood Cancermentioning
confidence: 99%